Formulation and in vitro evaluation of nifedipine- controlled release tablet: Influence of combination of hydrophylic and hydrophobic matrix forms - Derakhshandeh, Katayoun; Soleymani, Marzieh (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the present work was to develop controlled release matrix formulation of nifedipine and investigate the effects of both hydrophilic and hydrophobic polymers on in vitro drug release. Matrix tablets were prepared by wet granulation technique using different concentration of hydroxy propyl methyl cellulose (HPMC), ethyl cellulose (EC), compressible Eudragits (RSpo and RLpo) and their combination in different ratios to examine their influence on tablet properties and drug release profile.Tablets were evaluated by measurement of hardness, friability, content uniformity, weight variation and drug release pattern. Release studies were carried out using USP type II apparatus in 900 ml of sodium phosphate buffer (pH 7.4) with 0.5% (w/v) SDS. The amount of drug released was determined at 238 nm by UV-visible spectrophotometer. In vitro dissolution studies indicated that hydrophobic polymers significantly reduced the rate of drug release compared to hydrophilic ones in 12 hrs and combination of both polymers exhibited the best release profile to sustain the drug release for prolong period of time. As a result, the tablet containing HPMC:EC in ratio of 0.75:1 showed better controlled release pattern over a period of 12 hrs. In selected formulation, the calculated regression coefficients for release models fitted best to zero-order models